Pengaruh Partisipasi Anggaran, Asimetri Informasi, Penekanan Anggaran, dan Ambiguitas Peran Terhadap Budgetary Slack (Organisasi Perangkat Daerah Kota Yogyakarta) - Diansari, Rani Eka; Saraswati, Meilia (Akmenika: Jurnal Akuntansi dan Manajemen, 2020)
This study aims to examine the effect of budgetary participation, information asymmetry, budget emphasis, and role ambiguity on budgetary slack. This type of research is quantitative research. The population in this study is the Regional Organization of the Government of Yogyakarta City. Sample of research are 58 respondents involved in the preparation of the budget. The sampling selection using purposive sampling method. This research method is a descriptive analysis method with a survey approach. Method of data analysis used in this research is multiple linear regression mode.In the study, show that budgetary participation have significant positive effect on budgetary slack while information asymmetry, budget emphasis, and role ambiguity have no effect on budgetary slack on the Regional Organizations in the Yogyakarta City Government.Keywords: Budgetary Participation, Information Asymmetry, Budget Emphasis, Role Ambiguity, Budgetary Slack